Validation of salivary DNA extraction for non-invasive genetic sampling of Castor fiber birulai and assessment of DNA persistence on Salix turanica twigs - Zhu Linyin; Tian Xiangzhou; Zhang Chi; Zhang Yu; Wang Yanqing; He Chengbin; Zhong Linqiang (Conservation Genetics Resources, 2026)

Effects of Different Light Spectra on Oxidative Stress and Nutritional Quality of the Fish Plectropomus leopardus - Wensheng Li; Zheng Zhang; Baoliang Liu; Yingying Fang; Shuquan Cao; Wenyang Li; Yan Sun; Chengbin He; Chuanxin Zhang; Fan Fei (Fishes, 2024)
This study investigated the impacts of light spectra on oxidative stress and nutrient quality of the fish Plectropomus leopardus in indoor recirculating aquaculture systems. The fish (100 g ± 0.45 g [wet weight]) were cultures in five different light spectra (full-spectrum (400–800 nm), blue (450 nm), green (530 nm), red (630 nm), and dark) for 60 days. After experimentation, blood and muscle tissue were collected and analyzed for biochemical variables and nutritional quality. We demonstrated that the total cholesterol, triglycerides activities of P. leopardus in the dark groups were substantially elevated, relative to other groups (p

Risk assessment and spatial analysis of paralytic shellfish toxin (PST) concentrations and acute dietary exposure of commercially available shellfish in coastal areas in China - Shuwen Li; Jiao He; Jinfang Sun; Feng Pan; Pingping Zhou; Lei Zhang; Xin Yang; Chengbin Cao; Xiaojin Yu; Pei Cao (Food Control, 2024)

Suppression of mercury methylation in soil and methylmercury accumulation in rice by dissolved organic matter derived from sulfur-rich rape straw - Zhoujuan Zheng; Jie Hu; Tianrong He; Chengbin Liu; Xian Zhou; Deliang Yin (Environmental Pollution, 2024)

The significance of m6A RNA methylation regulators in diagnosis and subtype classification of HBV-related hepatocellular carcinoma - Qijuan Zang; Yalin Ju; Siyi Liu; Shaobo Wu; Chengbin Zhu; Liangru Liu; Weicheng Xu; Yingli He (Human Cell, 2024)

Rapid and sensitive quantification of cyclamate in beverages by miniature microplasma optical emission spectrometry - Jiang Jing; Siyu He; Jiahui Yang; Rui Yang; Yao Lin; Chengbin Zheng (Food Chemistry, 2023)

A universal strategy for large-scale and controlled fabrication of conductive mesoporous polymer monolayers - Facai Wei; Bowen Chen; Jianwei Fu; Qingguo He; Chengbin Jing; Jiangong Cheng; Miharu Eguchi; Jongbeom Na; Yusuke Yamauchi; Shaohua Liu (Chemical Engineering Journal, 2023)

A community effort to assess and improve computerized interpretation of 12-lead resting electrocardiogram - Zijian Ding; Guijin Wang; Huazhong Yang; Ping Zhang; Dapeng Fu; Zhen Yang; Xinkang Wang; Xia Wang; Zhourui Xia; Chiming Zhang; Wenjie Cai; Binhang Yuan; et al. (Medical & Biological Engineering & Computing, 2022)
Computerized interpretation of electrocardiogram plays an important role in daily cardiovascular healthcare. However, inaccurate interpretations lead to misdiagnoses and delay proper treatments. In this work, we built a high-quality Chinese 12-lead resting electrocardiogram dataset with 15,357 records, and called for a community effort to improve the performances of CIE through the China ECG AI Contest 2019. This dataset covers most types of ECG interpretations, including the normal type, 8 common abnormal types, and the other type which includes both uncommon abnormal and noise signals. Based on the Contest, we systematically assessed and analyzed a set of top-performing methods, most of which are deep neural networks, with both their commonalities and characteristics. This study establishes the benchmarks for computerized interpretation of 12-lead resting electrocardiogram and provides insights for the development of new methods.

Mortality risk of a future heat event across a subtropical city: implications for community planning and health policy - Hung Chak Ho; Ka Ming Wai; Minhao He; Ta-Chien Chan; Chengbin Deng; Man Sing Wong (Natural Hazards, 2020)

Regulatory effects of antitumor agent matrine on FOXO and PI3K-AKT pathway in castration-resistant prostate cancer cells - Qi Li; Hai Huang; Zheng He; Yi Sun; Yufeng Tang; Xiaohong Shang; Chengbin Wang (Science China Life Sciences, 2018)